Knockdown of zebrafish tmem242 enhances the production of ROS that signals to increase f9a expression resulting in DIC-like condition - Afnan Deebani; Jabila Mary; Sanchi Dhinoja; Ayah Al Qaryoute; Weam Fallatah; Pudur Jagadeeswaran (Scientific Reports)
Abstract Transmembrane proteins (TMEMs) are embedded in cell membranes and often have poorly understood functions. Our RNAseq analysis identified 89 tmem genes in zebrafish thrombocytes, leading to further investigation through knockdown experiments and gill bleeding assays. Knockdown of tmem242 significantly increased bleeding, indicating a role in hemostasis. While thrombocyte production and aggregation were unaffected, coagulation was impaired, with delayed fibrin and thrombus formation. Notably, mRNA levels of several clotting factor genes, including coagulation factor 5 (f5), coagulation factor 7 (f7), and coagulation factor 9a (f9a), were elevated, except for coagulation factor 8 (f8). Microthrombi were also observed in larvae after tmem242 knockdown. In parallel studies, impaired ATP synthase assembly in human cells lacking TMEM242 prompted us to hypothesize that reduced ATP synthase could elevate reactive oxygen species (ROS) levels, influencing clotting factor expression. Indeed, tmem242 knockdown increased ROS levels. Inhibition of ATP synthase with oligomycin elevated ROS and f9a transcripts, while ROS inhibition reduced f9a expression, suggesting ROS-mediated regulation. Further analysis revealed increased sirt6 and nrf2 transcripts after tmem242 knockdown, with their knockdown reducing f9a levels. These findings suggest that tmem242 depletion may impair ATP synthase, elevate ROS, upregulate sirt6 and nrf2, and increase f9a transcripts, potentially leading to bleeding tendencies similar to disseminated intravascular coagulation (DIC).